Study of Mothers' and Infants' Life Events Affecting Oral Health (SMILE) birth cohort study: cohort profile. Issue 10 (23rd October 2020) - Do, Loc G; Ha, Diep H; Bell, Lucinda K; Devenish, Gemma; Golley, Rebecca K; Leary, Sam D.; Manton, David J.; Thomson, W. Murray; Scott, Jane A; Spencer, A. John
Abstract : Purpose: The long-term goal of the Study of Mothers' and Infants' Life Events Affecting Oral Health (SMILE) birth cohort study is to identify and evaluate the relative importance and timing of critical factors that shape the oral health of young children. It will then evaluate those factors in their inter-relationship with socioeconomic influences. Participants: SMILE is a single-centre study conducted in Adelaide, Australia. All newborns at the main three public hospitals between July 2013 and August 2014 were eligible for inclusion. The final recruited sample at birth was 2181 mother/infant dyads. Participants were followed up with questionnaires when the child was 3 and 6 months of age, and 1, 2 and 5 years of age. Oral epidemiological examinations and anthropometric assessments were conducted at age 2 and 5 years. Findings to date: SMILE has contributed comprehensive data on dietary patterns of young children. Intakes of free sugars, core and discretionary foods and drinks have been detailed. There was a sharp increase in free sugars intake with age. Determinants of dietary patterns, oral health status and body weight during the first 5 years of life have been evaluated. Socioeconomic characteristics such as maternal education and household income and area-level socioeconomic profile influenced dietary patterns and oral health behaviours and status. Future plan: Funding has been obtained to conduct oral epidemiological examinations and anthropometric assessments at age 7–8 years. Plans are being developed to follow the cohort into adolescent years.